Analisis Faktor Penerbitan Obligasi Syariah (Sukuk) dan Penerbitan Saham Syariah Terhadap Kinerja Perusahaan di Jakarta Islamic Index 70 - Bella Jastacia; Ummu Salma Al Azizah; Rito Rito (IQTISHODUNA: Jurnal Ekonomi Islam, 2021)
This study aims to analyze the effect of the issuance of Islamic bonds (sukuk) and the issuance of Islamic stocks on company performance in the Jakarta Islamic Index 70. The issuance of Islamic bonds and Islamic stocks is an alternative for companies to obtain a capital structure in carrying out company operations and is expected to improve the company's performance. In terms of financial performance through Return On Assets (ROA), company stakeholders optimize Islamic capital market products to increase Islamic financial inclusion. Besides, it attracts investors to invest. This study uses a quantitative descriptive method, secondary data from companies listed in the Jakarta Islamic Index 70 years 2018-2020 using a purposive sampling method with Tobin's analysis and company age into 15 samples. Testing the hypothesis model using the classic assumption test and multiple regression tests to test the market reaction to the issuance of Sukuk and Islamic shares on the issuance variable using the issuance value, the number of shares outstanding, company leverage, company size, total debt, and company managerial ownership. The research resultsstated thatReturn on Assets (ROA) was affected bythe issuance value variable and the company's leverage in 0.00192 and 0.0373. The variables of the number of outstanding shares, total debt, firm size, and managerial ownership do not affect the value of ROA. However, all variables have a significant effect on the ROA value. The result shows that the issuance of Islamic bonds and Islamic stocks affects the company's performance.